FAKTOR YANG MEMPENGARUHI TURNOVER KARYAWAN DAN STRATEGI RETENSI SEBAGAI PENCEGAHAN TURNOVER KARYAWAN : SEBUAH TINJAUAN LITERATUR - Donny Agung Harvida, Chandra Wijaya (Universitas Riau, 2020)
Factors Affecting Employee Turnover and Retention Strategies as Prevention of Employee Turnover: A Literature Review. Turnover can be interpreted as the discharge of an employee from the company where he works. Turnover in organizations can lead to instability and uncertainty about labor conditions and will increase costs that must be incurred by the organization. Turnover can be experienced by organizations in the private and public sectors. The writing of this article uses the literature review data collection method for various reports, publications or news about employee turnover. There are several factors that influence employees in making decisions to stay or leave the organization, among others: employee factors, organizational factors and environmental factors. The organization needs to find out the factors that cause turnover in its organization, so that the organization can prevent turnover. Employee retention is the organization's strategy to maintain the potential employees of the organization to remain loyal to the organization. If the employee retention strategy is implemented well, employee turnover will be reduced.